Length–weight and length–length relationships for 135 fish species from the Xingu River (Amazon Basin, Brazil). (9th January 2015) - Giarrizzo, T.; de Sena Oliveira, R. R.; Costa Andrade, M.; Pedrosa Gonçalves, A.; Barbosa, T. A. P.; Martins, A. R.; Marques, D. K.; Brito dos Santos, J. L.; de Paula da Silva Frois, R.; Oliveira de Albuquerque, T. P.; Fogaça de Assis Montag, L.; Camargo, M.; et al.
Summary Length–weight (LWR) and length–length relationships (LLR) are presented for 135 freshwater fish species sampled by several types of fishing gear between April 2012 and July 2014 in the middle and lower Xingu River Basin, northern Brazil. The report represents the first references on LWRs and LLRs for 114 and 119 species, respectively, and also provides a new maximum size for 96 species.